Simulation of Anisotropic Deformation Behavior of Pressure Tubes During High Temperature Loading Conditions. (2017) - Syed, A.; Samal, M.K.; Bhasin, V.
Abstract: High temperature loading conditions occurring during postulated accident scenarios in a reactor may cause significant deformation of pressure tube in circumferential and longitudinal directions. Due to the anisotropic nature of Zirconium-2.5% Nb alloy, the deformation behaviour is different in different direction. In this paper, Hill's quadratic anisotropic yield function has been used. The anisotropic factors of yield function for the Indian pressure tube material have been obtained by using data of component level tests. Analytical models for simulation of ballooning and sagging deformation of pressure tube has been developed. Norton's creep parameters have been evaluated from experimental data and used as input to the constitutive relations for evaluating the longitudinal and transverse strains. Time taken by pressure tube to contact the calandria tube has been evaluated for different combination of thermal and internal pressure loading conditions. Results of the model have been compared with the experimental data.